Aplikasi Pemesanan Lapangan Olahraga Usman Harun Sport Center Berbasis Android dengan Metode First Come First Serve Menggunakan Android Studio dan Firebase - Saktiadji, Bayu Nugraha; Faizah, NM; Koryanto, Lucky (Computer Journal, 2023)
Usman Harun Sport Center is one of the Sport Centers under the auspices of the Jakarta Marine Base Marine Cooperative Primary which is engaged in business, in the form of Sports Field Rental. Until now, Field Orders are still done manually. The method used by the management of the Usman Harun Sport Center is currently inefficient. Therefore, this study has the objectives of (1) Designing a field booking application that can be easily and quickly accessed by customers via gadgets, (2) Designing a field ordering application that can be used by employees to update field availability status information, and (3) Designing a field booking application that can provide an overview of the facilities offered by the Usman Harun Sport Center. From this goal, the authors built and designed an Android-based Usman Harun Sport Center Sports Field Booking Application with the First Come First Serve Method Using Android Studio and Firebase. The final result of this research is to improve the quality and service for Prospective Customers for the Usman Harun Sport Center Sports Field.